Resistance of Local Acehnese Rice Lines to Xanthomonas Oryzae pv. Oryzae, the Causal Agent of Bacterial Leaf Blight Disease - Alfizar Alfizar; Lukman Hakim; Jihan Aura; Siti S Nasution; Syaukani Syaukani (Journal of Innovative and Creativity, 2025)
Bacterial leaf blight, caused by the bacterium Xanthomonas oryzae pv. oryzae, is a major problem for rice production in Indonesia. One way to control this disease is to use rice varieties with resistance. The study aims to obtain local Acehnese rice lines, improve them through inbred breeding, and use gamma-ray irradiation to control bacterial leaf blight. The study used a non-factorial Complete Random Design (CRD) with nine local Acehnese rice lines, namely Tinggong (T.35.7.5.7.1), Tinggong (T.35.7.5.1.1), Sambay Simeulue (US1), Sambay Simeulue (US2), Sigupai (UM69), Sigupai (UM18), Sikuneng Bireuen (UB5), Sikuneng Bireuen (UB9), and Ciherang varieties as comparisons, with three replicates. The incubation period and disease incidence were not significantly different between treatments, ranging from 4.33 to 5.66 days and from 39.28 to 57.03%, respectively. The highest disease severity was observed in the Sigupai rice strain (UM69) (47.37%), and the lowest in Sambay Simeulue (US2) (26.25%). The results indicate that the Aceh local rice lines fall into the moderately resistant category, namely Sambay Simeulue (US2), Tinggong (T.35.7.5.1.1) and Sambay Simeulue (US1). In contrast, the moderately susceptible categories are Sikuneng Bireuen (UB9), Sikuneng Bireuen (UB5), Ciherang variety (comparator), Tinggong (T.35.7.5.7.1), Sigupai (UM18) and Sigupai (UM69).